Histology of a Marfan aorta 4.5 years after personalized external aortic root support - Pepper, John (Eur J Cardiothorac Surg, 2015)
In 2008, a 26-year old man had personalized external aortic root support (PEARS) with a macroporous mesh. He was the 16th of 46 patients to have this operation. He had a typical Marfan habitus. His mother died of this disease as did his brother, with an aortic dissection. The patient himself died suddenly 4.5 years after his PEARS operation. At autopsy, there was no blood in the pericardium. The coronary orifices and proximal arteries were normal. His bicuspid aortic valve was minimally regurgitant as it was prior to operation and remained throughout follow-up. Macroscopically the implanted mesh was embedded in the adventitia and not separable from the aortic wall. Microscopically it was fully incorporated with collagen fibres as has been seen in our animal studies. The unsupported aortic arch showed some focal fragmentation of elastic fibres and a mild increase in mucopolysaccharides consistent with Marfan syndrome. These appearances were not present in the supported aortic root, which had the histological appearance of a normal aorta. He was the first patient to die with an implant. The histological appearances suggest the possibility that the incorporated support of the aortic root allowed recovery of the microstructure of the media.